Analisis Nilai dan Volume Transaksi Timah Pada Bursa Timah Indonesia Sebelum dan Setelah Kebijakan Multi Bursa - Wicaksena, Bagus (Cendekia Niaga, 2021)
The implementation of mandatory regulations of tin export through commodity multi-exchange has been considered effective in suppressing illegal tin trading practices, building transparency in transaction and export record, and creating added value for tin export. However, the essence of a multi-exchange policy should also promote the increasing in value and volume of tin transactions. This analysis aims to see the difference in the value and volume of tin transactions before and after the multi-exchange policy. By using the Paired Sample t-test, there are shown significant differences in value and volume of tin transactions whereby the value and volume transacted after the multi-exchange policy is relatively lower. The decrease in transaction value will affect the state tin royalty revenue. Interestingly, the decline in transaction value is driven by the high disparity between the value and volume of transactions between the two exchanges. Therefore, trade policies that support the consolidation of the tin market are urgently needed to optimize state royalty revenues.